Emerging cancer disease burden in a rural sub-Saharan African population: northeast Nigeria in focus - Ezenkwa, Uchenna S.; Lawan, Aliyu Ibrahim; Garbati, Musa Abubakar; Suleiman, Dauda E.; Katagum, Dauda A.; Kabir, Abba; Adamu, Adamu Isa; Modu, Abubakar Kolomi; Olanrewaju, Olaniyi David; Dachi, Rufai Abdu; Abdullahi, Yusuf Mohammed; Alkali, Muhammed; et al. (Frontiers in Oncology, 2024)
Introduction: Sub-Saharan Africa (SSA) is plagued by myriads of diseases, mostly infectious; but cancer disease burden is rising among non-communicable diseases. Nigeria has a high burden of cancer, but its remote underserved culturally-conserved populations have been understudied, a gap this study sought to fill. Methods: This was a cross-sectional multiinstitutional descriptive study of histologically diagnosed cancers over a four-year period (January 2019-December 2022) archived in the Departments of Pathology and Cancer Registries of six tertiary hospitals in the northeast of Nigeria. Data obtained included age at diagnosis, gender, tumour site and available cancer care infrastructure. Population data of the study region and its demographics was obtained from the National Population Commission and used to calculate incident rates for the population studied. Results: A total of 4,681 incident cancer cases were identified comprised of 2,770 females and 1,911 males. The median age at diagnosis for women was 45 years (range 1-95yrs), and 56 years (range 1-99yrs) for. Observed agespecific incidence rates (ASR) increased steadily for both genders reaching peaks in the age group 80 years and above with the highest ASR seen among males (321/100,000 persons) compared to females (215.5/100,000 persons). Breast, cervical, prostatic, colorectal and skin cancers were the five most common incident cancers. In females, breast, cervical, skin, ovarian and colorectal cancers were the top five malignancies; while prostate, haematolymphoid, skin, colorectal and urinary bladder cancers predominated in men. Conclusion: Remote SSA communities are witnessing rising cancer disease burden. Proactive control programs inclusive of advocacy, vaccination, screening, and improved diagnostics are needed.